MOLECULAR DETECTION OF ZIKA VIRUSES USING LAB-CHIP REAL-TIME RT-PCR SYSTEM - Watthanachockchai, Treewat; Pasomsub, Ekawat; Chantratita, Wasun; Pongstaporn, Wanida; Sukplang, Patamaporn; Thongmee, Acharawan (Interprofessional Journal of Health Sciences, 2023)
Zika virus (ZIKV) is the causative agent of Zika fever. The viruses are primarily transmitted to people through the bite of infected Aedes aegypti mosquitoes. Zika viruses can survive in the infected person for several months. Zika viral infection during pregnancy is a cause of congenital brain abnormality causing stillborn and microcephaly. It also causes severe symptoms in patients with the Guillain-Barre syndrome. Currently, the detection of ZIKV using real-time RT-PCR technique has some limitations. Therefore, the treatment and control of ZIKV epidemic are delayed. Lab-Chip technology is a new and faster method for ZIKV detection. In this study 232 suspected ZIKV cases were evaluated by the Lab-Chip real-time RT-PCR and the results were compared with real-time RT-PCR reference method and DNA sequencing. It was found that that the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, Likelihood Ratios for positive test (LR+), Likelihood Ratios for negative test (LR-), and diagnostic odds ratio (DOR) of the Lab-Chip real-time RT-PCR technique were 95.78%, 97.08%, 95.78%, 97.08%, 96.55%, 32.80, 0.0434, and 820, respectively. The limit of detection of this method was 125 cp/ml. In addition, when using Lab-Chip real-time RT-PCR for determination of ZIKV in other viral infected samples such as Adenovirus, Epstein Bar virus, Herpes simplex virus, Varicella zoster, Enterovirus, Human metapneumovirus, Influenza B, and Coronavirus, cross-reactivity was not found. In conclusion the Lab-Chip real-time RT-PCR technique shows high sensitivity and specificity and less time consuming for ZIKV detection.